Pancreatitis associated with azathioprine and 6-mercaptopurine use in Crohn's disease: a systematic review. Issue 5 (11th June 2020) - Gordon, Morris; Grafton-Clarke, Ciaran; Akobeng, Anthony; Macdonald, John; Chande, Nilesh; Hanauer, Stephen; Arnott, Ian
Abstract : Thiopurines are proven agents in the treatment of Crohn's disease. While pancreatitis is recognised as an adverse event associated with therapy, the effect size and morbidity of thiopurine-induced pancreatitis is not known. The aim of this systematic review and meta-analysis was to quantify the risk of pancreatitis with azathioprine and 6-mercaptopurine (6-MP) within Crohn's disease. We searched six electronic databases from inception to 29 October 2019. The primary outcomes measures were the occurrence of pancreatitis. We calculated pooled OR with corresponding 95% CIs for risk of pancreatitis. A number needed to harm analysis was performed. The search identified 4418 studies, of which 25 randomised controlled trials met the criteria for inclusion. The number of patients treated with azathioprine to cause an episode of pancreatitis was 36 (induction of remission) and 31 (maintenance of remission).The risk of pancreatitis in patients receiving azathioprine across all contexts was 3.80%, compared with a control risk of 0.2% (placebo) and 0.5% (5-aminosalicylic acid agents). There was no difference seen between 6-MP and placebo, although this was a low certainty result due to imprecision from very low event numbers and patient numbers. There is a probably increased occurrence of pancreatitis when azathioprine is used in Crohn's disease (moderate certainty), with incidence overall approximately 3.8%. Most cases are mild and resolve on cessation of therapy and no mortality was reported. There was no increased occurrence seen when using 6-MP, although this is a low certainty finding. PROSPERO prior to the study (CRD42019138065).